QUANTITATIVE AND QUALITATIVE TRACER TEST INTERPRETATION TO REEVALUATE REINJECTION STRATEGY IN LAHENDONG USING MOMENT ANALYSIS - Dwi Wahyono, Akbar
In reservoir management activities, tracer test is a prominent tool in getting a snapshot of inter well connectivity, in inferring subsurface fluids flow and in evaluating the reinjection program applied in geothermal field. One of the methods that can be used to tracer test analyis is Shook’s method of moment analysis. The method is based on accurate estimation of the tracer mean residence time which later be a fundamental parameter in calculating flow geometry and sweep efficiency of injected fluids. The incremental insights of the reservoir characteristics such as subsurface fluids flow and permeability distribution along the fault zone (qualitative interpretation) and the additional evaluation on the effect of injected cooler fluids from LHD-7 to the Northern and Southern production wells (quantitative interpretation) in Lahendong are the aims of this research by implementing moment anlysis on tracer interpretation. The result shows the homogenous behavior of flow – storage capacity plots (flow geometry) in all well pairs. This infers that damage zone which consist of small faults, fractures, veins, and folds is heavily controlling the fluids flow in the reservoir. Permeability structure type in Lahendong is dominated by distributed conduits with the presence of combined conduit-barrier in the vincinity of Lake Linau. Three models on how injected water travels through the reservoir have also been identified: by direct paths (streamlines) along fractures, through rock matrix and sweeping through a larger part of the reservoir. Sweeping the reservoir is dominant flow model compare to the smaller fraction of fluids which flow through the streamlines which are less than 4,5 % in all well pairs. However, evidently this is adequate in potentially harming the production wells in Northern cluster of LHD-5 and in Southern clusters of LHD-8, LHD-12 and LHD-18 with the thermal breakthrough. Four key problems regarding production-injection strategy along with its implication on the future reservoir management program have been successfully identified.